Association between smartphone screen time and exaggerated blood pressure response during treadmill exercise testing: a cross-sectional study - Muhammet Geneş; Cem Barçin (Blood Pressure)
Objective This study aimed to investigate the relationship between exaggerated hypertensive response to exercise (EHRE), mobile phone screen time and daily physical activity levels, with a focus on potential lifestyle-related factors that contribute to cardiovascular risk.Methods This observational case-control study enrolled 85 participants, who were categorised into an Exaggerated Hypertensive Response to Exercise (EHRE) group (n = 33) and a normotensive control group (n = 52). Participants underwent a standardised treadmill exercise test to identify EHRE. Objective data on daily mobile phone screen time and step counts were collected directly from the smartphones’ native tracking applications.Results Compared to controls, participants with EHRE exhibited significantly higher daily mobile phone screen time (6.1 ± 1.2 h/day vs. 4.7 ± 0.9 h/day; p < .001), greater weekly screen time in dim-light conditions (e.g. in bed at night) (14.5 ± 3.4 h/week vs. 7.0 ± 2.1 h/week; p < .001), a longer duration of mobile phone usage (19.7 ± 1.9 years vs. 17.7 ± 1.5 years; p = .002) and notably lower daily step counts (4120 ± 950 steps/day vs. 6830 ± 1120 steps/day; p < .001).Conclusion Increased mobile phone screen time and reduced physical activity levels were significantly associated with EHRE, suggesting that these factors are relevant as modifiable behavioural risk factors. These findings support the integration of digital behavioural metrics into preventive cardiovascular risk management strategies.